1999
DOI: 10.1161/01.atv.19.4.847
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Early Lipid Accumulation in ApoE-Deficient Mice

Abstract: Abstract-Apolipoprotein (apo) E-deficient mice develop severe hypercholesterolemia and have lesions that progress from fatty streaks to fibrous plaques distributed in lesion-prone areas throughout the aorta. Lesions develop in apoE-deficient mice on a regular chow diet and will occur faster on a diet higher in cholesterol. Examination of the aortas from these mice on a chow diet by high-resolution, freeze-etch electron microscopy demonstrated lipid retention in the intima by 3 weeks of age. Lipid was retained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 21 publications
0
93
0
4
Order By: Relevance
“…Monocyte attachment to endothelial cells of the aortic sinus in apoE-deficient mice was observed before obvious fatty streak formation. 36 Macrophages loaded with fluorescent microspheres injected intravenously into 40-week-old apoE-deficient mice adhered to all stages of atherosclerotic plaques, including mature calcified fibrous lesions. 37 Macrophages in the subendothelium may at first protect against atherosclerosis but later also contribute to lesion progression.…”
Section: Dong Et Al P-selectin In Advanced Atherosclerosis 2293mentioning
confidence: 99%
“…Monocyte attachment to endothelial cells of the aortic sinus in apoE-deficient mice was observed before obvious fatty streak formation. 36 Macrophages loaded with fluorescent microspheres injected intravenously into 40-week-old apoE-deficient mice adhered to all stages of atherosclerotic plaques, including mature calcified fibrous lesions. 37 Macrophages in the subendothelium may at first protect against atherosclerosis but later also contribute to lesion progression.…”
Section: Dong Et Al P-selectin In Advanced Atherosclerosis 2293mentioning
confidence: 99%
“…I nitiation of atherosclerosis in both humans 1 and experimental animals [2][3][4] is characterized by the appearance of extracellular lipid droplets in the proteoglycan (PG)-rich subendothelial layer. Experimental models have shown that similar droplets can be formed directly from LDL particles both in situ 2,5 and in vivo.…”
mentioning
confidence: 99%
“…39 A defining stage in the development of atherosclerotic lesions that precedes the attachment of monocytes to the vessel wall, is the accumulation of remnant lipoproteins on the intimal extracellular matrix which occurs as early as 3 weeks of age in apoE -/-mice. 46 The presence of low levels of apoE in the circulation may prevent the recruitment of the remnant lipoproteins to the vessel wall and therefore protect against the development of atherosclerosis. 45 This may explain how low levels of human apoE in the circulation of apoE -/-mice can protect against early lesion development.…”
Section: Figure 6 Reduction In Aortic Atherosclerotic Lesions In Apoementioning
confidence: 99%